Pemanfaatan Blooket untuk Evaluasi Pembelajaran Digital Berbasis Respon Kultural di Madrasah Aliyah Negeri 2 Jember - Agustin, Puspita Dian; Parto, Parto; Ali, Ayu Hidayanti; Murti, Fitri Nura (Pascasarjana, Universitas Negeri Gorontalo, 2024)
Evaluation is always an interesting topic to study, this study highlights the ability of MAN 2 Jember teachers to create or utilize digital applications to conduct evaluations. The method used is qualitative descriptive. The results of the questionnaire showed that 100% of teachers were interested in learning Blooket after conducting a simulation at the beginning of the implementation and felt that the application of Blooket for this evaluation had proven to increase their understanding of culture in Jember Regency as a cultural response and became one of the fun learning efforts by implementing gamification content. In addition, only 34.5% of the total 65.5% of teachers have used digitalization in learning evaluations so that similar training or socialization is still needed in schools. In conclusion, teachers need many practitioners to carry out similar activities in the counseling of learning applications to support learning activities and welcome the 5.0 revolution